2018
DOI: 10.1186/s12862-018-1157-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of evolutionary rates in the murine sperm proteome

Abstract: BackgroundProtein-coding genes expressed in sperm evolve at different rates. To gain deeper insight into the factors underlying this heterogeneity we examined the relative importance of a diverse set of previously described rate correlates in determining the evolution of murine sperm proteins.ResultsUsing partial rank correlations we detected several major rate indicators: Phyletic gene age, numbers of protein-protein interactions, and survival essentiality emerged as particularly important rate correlates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 82 publications
3
13
0
Order By: Relevance
“…Other studies have demonstrated that tissue specificity of expression can strongly influence the molecular evolution of reproductive proteins (Schumacher & Herlyn, 2018), in some cases more than mating system (Carnahan-Craig & Jensen-Seaman, 2014). Because our proteomic data did not contain information on tissue specificity on their own, we examined this dynamic with RNA-seq data.…”
Section: Evolution Of Tissue-specific and Malelimited Genesmentioning
confidence: 99%
“…Other studies have demonstrated that tissue specificity of expression can strongly influence the molecular evolution of reproductive proteins (Schumacher & Herlyn, 2018), in some cases more than mating system (Carnahan-Craig & Jensen-Seaman, 2014). Because our proteomic data did not contain information on tissue specificity on their own, we examined this dynamic with RNA-seq data.…”
Section: Evolution Of Tissue-specific and Malelimited Genesmentioning
confidence: 99%
“…In both BODY sets, numerous connections to diverse signaling pathways (e.g., M3K2/MAP3K2, AKT2, TKNK/TAC3) were in accordance with the complexity of the entire organism [Cheng et al, 2000;Sakamoto et al, 2006;Tusset et al, 2012]. Also, the fact that the annotations for SPERM did not contain specificities is unsurprising: After all, many sperm-expressed proteins exert their multiple functions in diverse tissues [Schumacher and Herlyn, 2018]. Nevertheless, SPERM also exhibited clear connections to re-production, as exemplified by TSG10 (TSGA10), which is mainly expressed in sperm tail, and VATE2 (ATP6V1E2; alias VMA4), which participates in acrosomal acidification [Sha et al, 2018;Futai et al, 2019].…”
Section: General Characteristics Of Protein Sets and Testis Specialtiesmentioning
confidence: 83%
“…Also, transient PPIs have a lesser conserving effect on sequence evolution than obligate ones [Mintseris and Weng, 2005]. Additionally, higher phyletic age and broader or early onset of expression associate with higher sequence conservation [Zhang and Li, 2004;Good and Nachman, 2005;Toll-Riera et al, 2012;Schumacher and Herlyn, 2018]. Moreover, longer 5′ and 3′ untranslated regions [Worth et al, 2009;Schumacher and Herlyn, 2018] as well as more posttranslational modifications and higher pleiotropy levels [Macek et al, 2008;Jancura and Marchiori, 2012;Schumacher et al, 2013] associate with lowered substitution rates.…”
Section: Validity Of Correlation Analyses Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, NCBI's OMIM (Online Mendelian Inheritance in Man) already lists more than 200 genetic conditions associated with male infertility, spanning from the most common manifestations to the rarest complex syndromes [Cariati et al, 2019]. However, the number of genes with potential fertility relevance is probably higher as illustrated by more than 6,200 proteins in sperm alone, which may at least partially influence male fertility [Shetty et al, 1999;Johnston et al, 2005;Schumacher et al, 2013;Amaral et al, 2014;Schumacher and Herlyn, 2018]. Beyond that, genes expressed in spermiogenesis stages and somatic testicular cells will play a role in fertility maintenance -and these are many.…”
mentioning
confidence: 99%